Graphene antibacterial material as well as preparation method and application thereof
By synthesizing nano silver oxide in situ through sonication and hydrothermal reaction in graphene oxide, the problems of poor dispersion uniformity and easy precipitation of nano copper oxide are solved, and the excellent antibacterial properties and good drug resistance of the composite material are achieved.
Patent Information
- Application Number
- CN202411446061.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-14
AI Technical Summary
During the preparation process, the existing graphene and nano-copper oxide composites have problems such as poor dispersion uniformity and easy precipitation of nano-copper oxide, which affects its antibacterial effect.
Through sonication and hydrothermal reaction, nano copper oxide is synthesized in situ in the layered structure of graphene oxide to ensure its uniform dispersion and stability in the composite material.
The excellent antibacterial properties and good drug resistance of graphene oxide/nanocopper oxide composite materials are achieved, and the agglomeration of nanocopper oxide is avoided, thereby improving the overall performance of the composite materials.
Smart Images

Figure BDA0005087765070000081 
Figure BDA0005087765070000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene composite materials, and in particular to a graphene antibacterial material and a preparation method and application thereof. Background Art
[0002] Graphene is a material with a single layer of carbon atoms in a hexagonal honeycomb lattice structure with sp2 hybrid orbitals. It has many unique properties, such as mechanical, electrical, thermal and optical properties. In addition, graphene also has excellent antibacterial properties.
[0003] The antibacterial principle of graphene mainly includes the following three aspects: (1) Mechanical effect: Graphene has an extremely high surface area and extremely thin thickness, and can kill bacteria through direct contact; the surface of graphene can cut the bacterial cell wall, preventing the normal metabolism and growth of bacteria, thereby achieving an antibacterial effect. (2) Oxidation: Graphene can undergo oxidation reactions in light and air to form a large amount of active oxygen and free radicals. These substances with extremely strong oxidizing effects can directly destroy the bacterial cell membrane and DNA molecules, thereby achieving an antibacterial effect. (3) Immune effect: Graphene has a regulatory effect on the cellular immune system, which can enhance the body's immunity and improve the body's resistance to bacteria, thereby achieving an antibacterial effect.
[0004] Both nano-silver and nano-copper oxide have antibacterial effects. Although the antibacterial effect of nano-copper oxide is not as good as that of nano-silver, nano-copper oxide has lower cost and higher safety. In addition, nano-copper oxide can provide lasting antibacterial effects in situations where long-term antibacterial applications are required. When nano-copper oxide comes into contact with bacteria, the copper oxide ions on its surface will enter the bacterial cells through adsorption, diffusion, etc., and interact with proteins, nucleic acids and other molecules in the cells, thereby destroying the integrity of the cell membrane. In addition, nano-copper oxide can also interact with biological molecules such as oxidoreductases, affecting their catalytic activity, thereby inhibiting the growth and reproduction of bacteria.
[0005] The composite material prepared by graphene and nano copper oxide combines the advantages of both graphene and nano copper oxide, which can not only improve the physical and chemical properties of the material, but also enhance its antibacterial effect, making it have a broad-spectrum antibacterial ability, while solving the problem of bacterial resistance. Since the surface properties of graphene and nano copper oxide are very different, the blending compatibility of the two is not good. Even if nano copper oxide can be dispersed in graphene by physical mixing, there are problems of poor dispersion uniformity and easy precipitation. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a graphene oxide / nano copper oxide composite material. The method comprises the following steps: ultrasonically treating deionized water, graphene oxide, water-soluble copper salt and urea so that the water-soluble copper salt and urea are quickly dissolved in water, and graphene oxide is uniformly dispersed in water. Then, in-situ synthesis of nano copper oxide in a graphene oxide layered structure is achieved through a hydrothermal reaction, so that the dispersion uniformity and stability of nano copper oxide in graphene oxide are ensured. The prepared graphene oxide / nano copper oxide composite material can be used as an antibacterial material.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] The first object of the present invention is to provide a method for preparing a graphene antibacterial material, comprising the following steps:
[0009] (1) adding graphene oxide, water-soluble copper salt and urea to deionized water, and ultrasonically treating the water to obtain a mixed solution;
[0010] (2) adding the mixed solution into a high pressure reactor for hydrothermal reaction;
[0011] (3) Centrifuging, washing, and drying the hydrothermal reaction product to obtain a graphene oxide / nano copper oxide composite material.
[0012] The second object of the present invention is to provide a graphene oxide / nano copper oxide composite material prepared by the aforementioned preparation method.
[0013] The third object of the present invention is to provide the use of the aforementioned graphene oxide / nano copper oxide composite material as an antibacterial material.
[0014] The beneficial effects of the present invention are as follows: the present invention synthesizes nano copper oxide in situ in the layered structure of graphene oxide through ultrasonic treatment technology and hydrothermal reaction, and the obtained graphene oxide / nano copper oxide composite material has excellent antibacterial performance and good drug resistance, and can solve the problem that nano copper oxide is easy to precipitate and agglomerate when directly preparing the graphene oxide / nano copper oxide composite material from graphene oxide and nano copper oxide in a blending manner, thereby enabling graphene oxide and nano copper oxide to better exert their composite effect. DETAILED DESCRIPTION
[0015] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0016] The present invention provides a method for preparing a graphene antibacterial material, comprising the following steps:
[0017] (1) adding graphene oxide, water-soluble copper salt and urea to deionized water, and ultrasonically treating the water to obtain a mixed solution;
[0018] (2) adding the mixed solution into a high pressure reactor for hydrothermal reaction;
[0019] (3) Centrifuging, washing, and drying the hydrothermal reaction product to obtain a graphene oxide / nano copper oxide composite material.
[0020] Furthermore, the water-soluble copper salt is selected from at least one of copper nitrate and copper sulfate. In the present invention, water is used as the reaction solvent, which can not only reduce the cost but also improve the environmental friendliness of the process. When water is used as the reaction solvent, a water-soluble copper salt is correspondingly selected as the raw material for preparing nano copper oxide.
[0021] Further, the molar ratio of the water-soluble copper salt to urea is 2:(1-1.5). Under hydrothermal conditions, the copper salt reacts with urea to generate basic copper carbonate, and the basic copper carbonate decomposes to generate nano copper oxide. The molar ratio of the water-soluble copper salt to urea can be 2:1, 2:1.1, 2:1.2, 2:1.3, 2:1.4, 2:1.5 or any value in the range formed by any two of the above ratios.
[0022] Furthermore, the mass ratio of graphene oxide to water-soluble copper salt is (10-20):(10-20). For example, it can be 10:10, 10:15, 10:20, 15:10, 15:15, 15:20, 20:10, 20:15, 20:20 or any value in the range formed by any two of the above ratios.
[0023] Furthermore, the ultrasonic frequency of the ultrasonic treatment is 20-40kHz, the ultrasonic power is 100-500W, and the ultrasonic time is 5-15min. The ultrasonic treatment accelerates the dissolution rate of water-soluble raw materials and improves the dispersion effect of water-insoluble raw materials by generating cavitation effect and mechanical vibration.
[0024] Furthermore, the reaction temperature of the hydrothermal reaction is 125-135° C., and the reaction time is 2-5 hours. Although the hydrothermal method belongs to conventional technical means, the hydrothermal reaction conditions are the key factors affecting the structural morphology and performance of the product, and determine the application field and application effect of the product.
[0025] Furthermore, the washing is performed with deionized water until neutrality is achieved, and the unreacted water-soluble raw materials and water-soluble byproducts generated by the reaction are removed by water washing.
[0026] Furthermore, the drying is oven drying or freeze drying. When selecting a drying method, it should be considered whether it will damage the graphene structure.
[0027] The present invention also provides a method for preparing a graphene antibacterial material, comprising the following steps:
[0028] (1) adding graphene oxide, water-soluble copper salt, urea and 2-(methyl-2-propylene-1-ylamino)ethanol to deionized water, and ultrasonically treating the water to obtain a mixed solution;
[0029] (2) adding the mixed solution and the water-soluble initiator into a high-pressure reactor for hydrothermal reaction;
[0030] (3) Centrifuging, washing, and drying the hydrothermal reaction product to obtain a graphene oxide / nano copper oxide composite material.
[0031] Furthermore, the water-soluble copper salt is selected from at least one of copper nitrate and copper sulfate.
[0032] Furthermore, the molar ratio of the water-soluble copper salt to urea is 2:(1-1.5).
[0033] Furthermore, the mass ratio of the graphene oxide to the water-soluble copper salt and the auxiliary agent is (10-20):(10-20):(1-10).
[0034] Furthermore, the ultrasonic treatment has an ultrasonic frequency of 20 to 40 kHz, an ultrasonic power of 100 to 500 W, and an ultrasonic time of 5 to 15 min.
[0035] Furthermore, the reaction temperature of the hydrothermal reaction is 125-135° C., and the reaction time is 2-5 hours.
[0036] Furthermore, the washing is washing with deionized water until neutral.
[0037] Furthermore, the drying is oven drying or freeze drying.
[0038] Furthermore, the amount of 2-(methyl-2-propylene-1-ylamino)ethanol is 10-20% of the mass of graphene oxide, for example, 10%, 12%, 14%, 16%, 18%, 20% or any value within the range formed by any two ratios of the above.
[0039] Furthermore, the water-soluble initiator is azobisisobutylamidine hydrochloride or azobisisobutylimidazoline hydrochloride.
[0040] Furthermore, the amount of the water-soluble initiator used is 0.1-1% of the mass of 2-(methyl-2-propylene-1-ylamino)ethanol.
[0041] In step (1), 2-(methyl-2-propylene-1-ylamino)ethanol plays the role of a dispersant. During ultrasonic treatment, its dispersing effect is utilized to promote the uniform dispersion of graphene oxide in a mixed solution consisting of a water-soluble copper salt and urea, and the in-situ synthesis of nano-copper oxide in the graphene oxide layered structure is achieved through a hydrothermal reaction, thereby improving the dispersion uniformity of nano-copper oxide on the graphene oxide.
[0042] In step (2), under the action of an initiator, the polymer generated by the polymerization reaction of 2-(methyl-2-propylene-1-ylamino)ethanol plays the role of an adhesive, and the adhesion of the nano-copper oxide on the graphene oxide is enhanced by utilizing the bonding effect thereof, so that more nano-copper oxide is loaded on the graphene oxide, the utilization rate of the copper salt is improved, and the composite effect of the graphene oxide and the nano-copper oxide is enhanced, and the stable loading of the nano-copper oxide on the graphene oxide is achieved, thereby avoiding the problem that the nano-copper oxide falls off from the graphene oxide during the centrifugation and washing process of the post-treatment, thereby affecting the composite effect.
[0043] The present invention also provides a graphene oxide / nano copper oxide composite material prepared by the above-mentioned preparation method.
[0044] The present invention also provides the use of the aforementioned graphene oxide / nano copper oxide composite material as an antibacterial material.
[0045] The sources of some raw materials in the following examples and comparative examples are described:
[0046] Graphene oxide was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., with a diameter of 0.5-3 μm, a thickness of 0.55-1.2 nm, and a content of >99 wt%.
[0047] Polyvinyl alcohol was purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd., with a viscosity of 20-25 mPa.S.
[0048] Nano copper oxide was purchased from Beasley New Materials (Suzhou) Co., Ltd., with an average particle size of 20 nm and a specific surface area of 140 m 2 / g.
[0049] Example 1
[0050] (1) 150 g of graphene oxide, 100 g of copper nitrate and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W, and an ultrasonic time of 10 min to obtain a mixed solution.
[0051] (2) The mixed solution was added into a high pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for a reaction time of 3 h.
[0052] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0053] Example 2
[0054] (1) 200 g of graphene oxide, 100 g of copper nitrate and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1.5, and ultrasonic treatment was performed at an ultrasonic frequency of 20 kHz, an ultrasonic power of 200 W, and an ultrasonic time of 12 min to obtain a mixed solution.
[0055] (2) The mixed solution was added into a high pressure reactor for hydrothermal reaction at a reaction temperature of 125° C. for a reaction time of 4 h.
[0056] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and dried in an oven to obtain a graphene oxide / nano copper oxide composite material.
[0057] Example 3
[0058] (1) 100 g of graphene oxide, 100 g of copper sulfate and urea were added to 500 mL of deionized water, wherein the molar ratio of copper sulfate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 40 kHz, an ultrasonic power of 250 W, and an ultrasonic time of 15 min to obtain a mixed solution.
[0059] (2) The mixed solution was added into a high pressure reactor for hydrothermal reaction at a reaction temperature of 135° C. for a reaction time of 2 h.
[0060] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0061] Example 4
[0062] (1) 200 g of graphene oxide, 150 g of copper sulfate and urea were added to 500 mL of deionized water, wherein the molar ratio of copper sulfate to urea was 2:1.2, and ultrasonic treatment was performed at an ultrasonic frequency of 28 kHz, an ultrasonic power of 400 W, and an ultrasonic time of 5 min to obtain a mixed solution.
[0063] (2) The mixed solution was added into a high pressure reactor for hydrothermal reaction at a reaction temperature of 120° C. for a reaction time of 5 h.
[0064] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and dried in an oven to obtain a graphene oxide / nano copper oxide composite material.
[0065] Example 5
[0066] The method of Example 1 is followed, except that 2-(methyl-2-propen-1-ylamino)ethanol and azobisisobutylamidine hydrochloride are added in step (1) and step (2), respectively.
[0067] (1) 150 g of graphene oxide, 100 g of copper nitrate, 15 g of 2-(methyl-2-propylene-1-ylamino)ethanol and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W, and an ultrasonic time of 10 min to obtain a mixed solution.
[0068] (2) The mixed solution and 0.5% by weight of azobisisobutylamidine hydrochloride of 2-(methyl-2-propylene-1-ylamino)ethanol were added to a high-pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for 3 h.
[0069] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0070] Example 6
[0071] The method of Example 1 is followed, except that 2-(methyl-2-propen-1-ylamino)ethanol and azobisisobutylamidine hydrochloride are added in step (1) and step (2), respectively.
[0072] (1) 150 g of graphene oxide, 100 g of copper nitrate, 30 g of 2-(methyl-2-propylene-1-ylamino)ethanol and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W, and an ultrasonic time of 10 min to obtain a mixed solution.
[0073] (2) The mixed solution and 0.5% by weight of azobisisobutylamidine hydrochloride of 2-(methyl-2-propylene-1-ylamino)ethanol were added to a high-pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for 3 h.
[0074] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0075] Example 7
[0076] The method of Example 6 is followed, except that 2-(methyl-2-propen-1-ylamino)ethanol and azobisisobutylimidazoline hydrochloride are added in step (1) and step (2), respectively.
[0077] (1) 150 g of graphene oxide, 100 g of copper nitrate, 30 g of 2-(methyl-2-propylene-1-ylamino)ethanol and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W, and an ultrasonic time of 10 min to obtain a mixed solution.
[0078] (2) The mixed solution and 0.5% by weight of azobisisobutylimidazoline hydrochloride of 2-(methyl-2-propylene-1-ylamino)ethanol were added to a high-pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for 3 h.
[0079] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0080] Comparative Example 1
[0081] The method of Example 6 is followed, except that N-hydroxyethyl acrylamide and azobisisobutylamidine hydrochloride are added in step (1) and step (2), respectively.
[0082] (1) 150 g of graphene oxide, 100 g of copper nitrate, 30 g of N-hydroxyethyl acrylamide and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W, and an ultrasonic time of 10 min to obtain a mixed solution.
[0083] (2) The mixed solution and 0.5% by weight of azobisisobutylamidine hydrochloride of N-hydroxyethylacrylamide were added to a high-pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for 3 h.
[0084] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0085] Comparative Example 2
[0086] The method of Example 6 is followed, except that polyvinyl alcohol is added in step (1).
[0087] (1) 150 g of graphene oxide, 100 g of copper nitrate, 30 g of polyvinyl alcohol and urea were added to 500 mL of deionized water, wherein the molar ratio of copper nitrate to urea was 2:1, and ultrasonic treatment was performed at an ultrasonic frequency of 25 kHz, an ultrasonic power of 300 W and an ultrasonic time of 10 min to obtain a mixed solution.
[0088] (2) The mixed solution was added into a high pressure reactor for hydrothermal reaction at a reaction temperature of 130° C. for a reaction time of 3 h.
[0089] (3) The hydrothermal reaction product is centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a graphene oxide / nano-copper oxide composite material.
[0090] The nano-copper oxide loading capacity of the graphene oxide / nano-copper oxide composite materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 was tested, and the results are shown in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] As can be seen from Table 1, the present invention can significantly increase the loading amount of nano-copper oxide on graphene oxide and improve the composite effect of graphene oxide and nano-copper oxide by respectively using 2-(methyl-2-propylene-1-ylamino)ethanol and its polymer as a dispersant and a binder.
[0095] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a graphene antibacterial material, characterized in that: The following steps are involved: (1) adding graphene oxide, water-soluble copper salt and urea to deionized water, and ultrasonically treating the water to obtain a mixed solution; (2) adding the mixed solution into a high pressure reactor for hydrothermal reaction; (3) Centrifuging, washing, and drying the hydrothermal reaction product to obtain a graphene oxide / nano copper oxide composite material.
2. The preparation method according to claim 1, characterized in that: The water-soluble copper salt is selected from at least one of copper nitrate and copper sulfate.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the water-soluble copper salt to urea is 2:(1-1.5).
4. The preparation method according to claim 1, characterized in that: The mass ratio of the graphene oxide to the water-soluble copper salt is (10-20):(10-20).
5. The preparation method according to claim 1, characterized in that: The ultrasonic treatment has an ultrasonic frequency of 20 to 40 kHz, an ultrasonic power of 100 to 500 W, and an ultrasonic time of 5 to 15 min.
6. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 125-135° C., and the reaction time is 2-5 hours.
7. The preparation method according to claim 1, characterized in that: The washing is performed by washing with deionized water until the mixture becomes neutral.
8. The preparation method according to claim 1, characterized in that: The drying is oven drying or freeze drying.
9. A graphene oxide / nano copper oxide composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the graphene oxide / nano copper oxide composite material according to claim 9 as an antibacterial material.